Task design for graphs: rethink multiple representations with variation theory. Issue 2 (3rd April 2022) - Johnson, Heather Lynn
ABSTRACT: It is well known that students benefit from opportunities to interpret and create different representations (e.g., diagrams, graphs, tables, symbols) of mathematical ideas. Employing Marton's Variation theory as a lens, I argue for an expansion of the use of multiple representations in task design for graphs: Incorporate two different forms of the same type of graph to represent a relationship between variables in a situation. With this approach, designers, teachers, and researchers can engineer opportunities for students to discern, or separate, features of representation systems, such as the Cartesian coordinate system, and in turn, promote students' mathematical reasoning.